Generation and characterization of human osteoarthritis cartilage-derived mesenchymal stem cells by modified sample processing and culture method - Algraittee, Satar Jabbar Rahi; Lawal, Hamza; Boroojerdi, Mohadese Hashem; Sarmadi, Vahid Hosseinpour; Maqbool, Maryam; Che Hamzah, Fahrudin; Vellasamy, Shalini; John, Cini Mathew; Ling, King Hwa; Ramasamy, Rajesh (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Introduction: Mesenchymal stem cells (MSCs) can be isolated from different tissue sources, and show a high differentiation capacity towards osteogenic, adipogenic, chondrogenic, neurogenic and myogenic lineages upon a specific induction. Although the retrieval of MSCs from normal tissues is very straightforward, yet it could be challenging in degenerative conditions that limit the expansion of stem cells such as osteoarthritis. Thus, this study aimed to establish human MSCs culture from osteoarthritic cartilage (OA hC-MSCs) by optimising the sample processing and culture techniques. Methods: Human osteoarthritis knee cartilage samples were obtained (2-4 g) from 8 patients with a mean age of 62.75 years old during the joint replacement surgery. A conventional culture method carried along with the modified method where the period of enzyme digestion and serial plating culture procedure were incorporated. Results: The modified culture method has significantly increased the number of single cells twice after the sample processing. The time taken to form colonies and achieve confluence was also reduced when samples subjected to the modified method. The number of cell yields after passage 0 for the conventional and modified methods were 3.05±0.31 and 6.10±0.42 million cells, respectively. The adherent cells generated under these two conditions comply with criteria for MSCs in term of immunophenotyping and mesodermal differentiation. Conclusions: The current modified method enhances the production of MSCs and could be opted for samples that known to have reduced or defective stem cell pool which may impede the in vitro cell expansion.